A homologue of the Parkinson's disease-associated protein LRRK2 undergoes a monomer-dimer transition during GTP turnover. Issue 1 (December 2017) - Deyaert, Egon; Wauters, Lina; Guaitoli, Giambattista; Konijnenberg, Albert; Leemans, Margaux; Terheyden, Susanne; Petrovic, Arsen; Gallardo, Rodrigo; Nederveen-Schippers, Laura; Athanasopoulos, Panagiotis; Pots, Henderikus; Van Haastert, Peter; et al.
Abstract Mutations in LRRK2 are a common cause of genetic Parkinson's disease (PD). LRRK2 is a multi-domain Roco protein, harbouring kinase and GTPase activity. In analogy with a bacterial homologue, LRRK2 was proposed to act as a GTPase activated by dimerization (GAD), while recent reports suggest LRRK2 to exist under a monomeric and dimeric form in vivo. It is however unknown how LRRK2 oligomerization is regulated. Here, we show that oligomerization of a homologous bacterial Roco protein depends on the nucleotide load. The protein is mainly dimeric in the nucleotide-free and GDP-bound states, while it forms monomers upon GTP binding, leading to a monomer-dimer cycle during GTP hydrolysis. An analogue of a PD-associated mutation stabilizes the dimer and decreases the GTPase activity. This work thus provides insights into the conformational cycle of Roco proteins and suggests a link between oligomerization and disease-associated mutations in LRRK2. The Parkinson's disease‐associated LRRK2 protein is a multidomain Roco protein with GTPase activity. Here the authors use a multidisciplinary approach to characterize the GTPase mechanism of a homologous bacterial Roco protein and give mechanistic insights into disease-causing LRRK2 mutations.